2017
DOI: 10.1111/ene.13355
|View full text |Cite
|
Sign up to set email alerts
|

John Cunningham virus conversion in relation to natalizumab concentration in multiple sclerosis patients

Abstract: Higher natalizumab concentrations do not explain the increased JCV seroconversion rate in natalizumab treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…According to our results, during NTZ treatment, patients showed a statistically significant increase in their JCV index (1.20 vs 1.90, p =0.0009) and NTZ treatment was associated with a significant percentage of patients (16.5%) seroconverted to a positive status. Similar results have been reported from other study in literature in which the annualized seroconversion rate has been described as 6-7% in the first year of NTZ therapy, progressing to 10-25% after 4 years of continuous treatment with this drug [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…According to our results, during NTZ treatment, patients showed a statistically significant increase in their JCV index (1.20 vs 1.90, p =0.0009) and NTZ treatment was associated with a significant percentage of patients (16.5%) seroconverted to a positive status. Similar results have been reported from other study in literature in which the annualized seroconversion rate has been described as 6-7% in the first year of NTZ therapy, progressing to 10-25% after 4 years of continuous treatment with this drug [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…Seropositivity for JCV may be subject to a variety of influences and the values reported by different authors may therefore be somewhat skewed. For example, some large studies did not find any association between JCV positivity and the previous use of natalizumab or other immunosuppressive drugs [ 15 , 32 ]. Other authors reported the contrary, finding that seroconversion rates increased by more than 8.0% per year of use of natalizumab [ 21 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variable median results of NAT free circulating levels observed among studies (from 18 to 51 μg/ml) may be assay dependent, but a common characteristics noted within each study was the high variability among patients (less than 4 μg and up to 100 or 200 μg) ( 71 , 74 , 75 ). No clear relationship has been evidenced to identify factors involved in this heterogeneity although body weight might contribute ( 76 , 77 ). Nevertheless, for a given patient, trough levels soon reach a plateau and remain stable whatever the number of infusions ( 9 ) and for more than 90% of them were over 10 μg/ml ( 78 ).…”
Section: Drug Monitoringmentioning
confidence: 99%
“…No specific biologic risk linked to NAT properties has been definitively identified in this susceptibility, which is also observed in other immunosuppression states either related to HIV or monoclonal antibody treatments or other DMT. In the context of NAT, no drug overdose was noticed at the time of infection ( 77 ) and risk evaluation remained to be assessed on treatment duration and anti JC antibody status. In order to limit the risk of PML, EID protocols seem to maintain a sufficient efficacy, although the real benefit on large cohorts has not yet been reported, and the ongoing NOVA study might contribute to this evaluation ( 91 ).…”
Section: Drug Monitoringmentioning
confidence: 99%